Classroom Management Strategy in Implementing the Merdeka Curriculum (Independent Curriculum) in Primary Education Institutions - Mubarok, Ramdanil; Sholeh, Makherus; Irayana, Ika (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2023)
This research aims to analyze class management strategies, class management processes, and class management problems in implementing the Merdeka curriculum in basic education institutions. This research was conducted at MIN 1 East Kutai. The method used is the descriptive qualitative research method. There were 8 informants in this study: the deputy principal for curriculum, class I, II, IV, and V teachers, and three invalid teachers. The research results show that classroom management strategies involve collaboration between teachers and students in lesson planning, selection of diverse materials, open and active learning, and emphasis on formative assessment. The class management process is carried out through initial assessments, preparing plans, implementation through understanding the goals and principles of the independent curriculum, determining learning objectives, using appropriate methods, facilitating students in creating study groups, providing assistance regarding conflicts and challenges in learning, and evaluating learning. The problems include too many students in one class, lack of student learning independence, lack of appropriate learning media, uneven understanding, difficulty managing time, lack of communication, and insufficient resources and understanding of the Merdeka curriculum. The practical implications of this research can help educators develop more effective approaches to managing the classroom and designing classroom management that allows students to reach their maximum potential in an Merdeka curriculum.